Peran Website dalam Meningkatkan Citra dan Branding Sekolah - Arief Rahman Hakim; Nayoan, Rafael; Istha Istha; Louise Gabriella (Lembaga Pengembangan Kinerja Dosen, 2026)
This study explores the role of school websites in shaping institutional image and branding in the digital era. Using a descriptive qualitative approach through a structured literature review, the research synthesizes national and international publications from 2020–2025 related to educational websites, institutional reputation, and school branding. Data were obtained through systematic database searches and document selection using purposive and snowball techniques. Thematic analysis identified three core insights: (1) website design and quality serve as representations of institutional identity, (2) authentic and communicative digital content enhances public engagement, and (3) stakeholder trust is shaped by the transparency, completeness, and timeliness of website information. These findings affirm the strategic importance of school websites in branding practices and emphasize the need for professional digital information management. Theoretically, the study integrates brand identity and website quality into the discourse on educational branding, while practically offering guidance for schools to develop credible, user-centered websites. Further research is recommended to examine user experiences directly.